Relationship selling - Johnston, Mark W.; Marshall, Greg W. (New York, 2008)
This book focuses on securing, building, and maintaining long-term relationships with profitable customers, highlighting the salesperson as an essential element in communicating value to customers. From its numerous role-plays and pedagogical aids to its student-friendly style and stellar teaching support, Relationship Selling is a favorite of students and instructors alike.
Keywords: Relationship marketing; Selling